Anchor Points Our Imbedded Cultural Lifelines: Each To His Own Culture - Thomson, Wendy (British Journal of Healthcare and Medical Research, 2024)
“We shall shortly be making our descent into London Heath Row; the temperature is 14 degrees. On behalf of the crew, we hope you have had a pleasant journey “The captain rounded off. The fact was I couldn’t have cared less what the temperature was, it could have been a raging hurricane or a blizzard for all I cared. I was just so pleased and relieved at the prospect of touch down: the bump when rubber and tarmac meet. To be back in my own country - England. I had missed my roots and everything English. I had accepted and respected that I was an interloper in South Africa, it wasn’t my country, it belonged to them - I had no rights - I had to conform. I was an alien. I had to toe the line it was the right thing to do. But I was homesick for my own people in my own country, where my family had lived for centuries — the English, a small island nation which had made its mark with a punch above its weight: Patriotic and willing to risk their lives for the country they loved, and their ancestors had helped to evolve and create. Albeit, rebellious, critical, and disagreeable when England was being mismanaged. But inventive resolute stoical when it mattered most.